Evaluating renewable energy choices among rural communities in Nigeria. An insight for energy policy - Okwanya, Innocent; Alhassan, Abdulkareem; Migap, Job Pristine; Adeka Sunday, Simon (Emerald Group Publishing Ltd, 2021)
Purpose This study aims to examine the effects of policy incentives and cost on the choice and use of renewable energy in North-Central Nigeria. Design/methodology/approach The data for this study are collected from a sample of 290 respondents drawn from across 6 states in North-Central Nigeria, including the Federal Capital Territory. This study uses descriptive statistics and multinomial logistic regression to analyze the data. Findings The findings reveal that there is a huge potential demand for renewable energy sources (particularly solar photovoltaic) in the rural communities in Nigeria. It also indicates a positive and highly significant relationship between the level of awareness, availability and income and the use (consumption) of renewable energy sources among the rural communities. Furthermore, the cost of installation and maintenance of renewable energy, its reliability and availability are significant determinants of renewable energy choices among rural inhabitants in Nigeria. Practical implications The authors submit that inefficient policy strategies, high cost of installation and lack of awareness remain the major hindrances to the use of more efficient renewable energy sources. From a policy point of view, a viable strategy for effective use of renewable energy sources is the involvement of government, development partners and agencies for the funding of renewable energy technology in the rural sector of the country. The usage of modern renewable energy would increase if policy incentives are aimed at covering parts of the maintenance and installation cost of renewable energy users. The authors recommend that apart from creating awareness on the benefits of renewable energy, policymakers should provide a desirable policy environment for private energy firms to supply renewable energy at an affordable cost to the rural communities in Nigeria. Social implications A majority of the rural households in Nigeria, as shown in this article, are poor and therefore use firewood as their main source of cooking energy because of the cost of renewable energy. Originality/value Despite the abundance of renewable energy sources and government effort at improving renewable energy use, more than 15 million people live without access to electricity and 54 million are without modern energy services for cooking and lightening in Nigeria. A total of 61% of these people live in rural areas. Therefore, this study is novel in providing energy policy insights for rural communities in North-Central Nigeria.
Keywords: Renewable energy; Rural energy use; Policy incentives; Solar photovoltaic; Biomass; Hydropower; Cost; Regression; Mail questionnaires; O38; P25; P28; Q42; Q48